Fiber grating humidity sensor and preparation method thereof
By using a moisture-sensitive coating layer modification solution containing potassium acetate and polyacrylic acid in the fiber grating humidity sensor for surface modification treatment, the problem of separation and moisture hysteresis of the coating layer and fiber cladding is solved, and the stability of the sensor is improved and service life, and enhance measurement accuracy in high humidity environments.
Patent Information
- Application Number
- CN202410637985.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-05-22
AI Technical Summary
Existing fiber grating humidity sensors are prone to separation of coating and fiber cladding, moisture hysteresis and short service life in high humidity and high temperature environments, which affects its measurement accuracy and stability.
The surface modification treatment of the Bragg grating of the polyimide-coated optical fibers is carried out using a moisture-sensitive coating layer modification solution containing potassium acetate and polyacrylic acid. The polyimide coating layer and optical fiber are enhanced by annealing and stress release treatment. The adhesion effect of the gate cladding is improved, and the hydrophobicity and pore space of the material are increased, and the water absorption rate and sensitivity are increased.
It improves the adhesion stability of the coating layer of the fiber grating humidity sensor and the fiber, reduces moisture hysteresis, extends the service life of the sensor, and improves the measurement accuracy and stability in high humidity environments.
Smart Images

Figure CN119124232A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sensor monitoring technology, and more specifically, relates to a fiber grating humidity sensor and a preparation method thereof. Background Art
[0002] The fuel cell integrated test bench has a large gas supply flow rate and a fast temperature change rate. The hydrothermal state of the test bench, such as the internal temperature and membrane water content, is closely related to the performance and life of the fuel cell stack system. Therefore, real-time monitoring of the temperature and relative humidity of the gas entering the fuel cell stack from the thermal management system and humidification system of the integrated test bench is of great significance for high-precision integrated testing and diagnosis of fuel cells.
[0003] At present, the comprehensive test system of fuel cells widely uses MEMS capacitive humidity sensors for relative humidity detection. The sensor probe is composed of a silicon substrate, a humidity-sensitive electrolyte layer, and a moisture-permeable electrode. When the relative humidity around the sensor probe changes, the humidity-sensitive dielectric capacitance changes accordingly, and the MEMS capacitive sensor converts the capacitance measurement into the circuit signal required for the output. However, most MEMS capacitive humidity sensors are sheet-like structures. In a high-humidity environment, condensation is easily formed inside the sensor due to temperature fluctuations, and adheres to the humidity-sensitive electrolyte, causing the relative humidity measurement to fail.
[0004] Optical fiber has the advantages of anti-electromagnetic interference, small size, and corrosion resistance. The optical fiber humidity sensor formed by combining optical fiber with humidity-sensitive film may meet the needs of relative humidity measurement in some extreme environments. The performance of different humidity-sensitive films varies greatly, and the mechanism of action is also different. Light intensity modulation optical fiber sensors and interference optical fiber sensors are to coat humidity-sensitive films on the end face of optical fiber for sensing, and the change of ambient humidity is linked to the light intensity and optical path difference of the transmitted light for humidity sensing. However, in actual applications, the light intensity or optical path difference is easily interfered by external factors such as pressure and temperature, resulting in large errors in humidity measurement values.
[0005] Fiber Bragg grating humidity sensor is a humidity-sensitive film coated around the Bragg grating. The polymer film absorbs water and expands in a humid environment. The stress generated by the expansion will drive the change of the grating period, and then change the central wavelength of the grating reflection peak. By monitoring the change of the central wavelength, the change of the relative humidity of the environment can be reflected. This type of sensor has a linear response to the ambient humidity and is highly susceptible to environmental interference. It can be used for high humidity detection to a certain extent, but there are still problems such as separation of the coating and the optical fiber cladding, high moisture hysteresis and short service life when exposed to high humidity and high temperature environment for a long time. Summary of the invention
[0006] The object of the present invention is to provide a fiber grating humidity sensor and a preparation method thereof, so as to improve the stability of the coating layer of the fiber grating humidity sensor and the optical fiber adhesion, reduce hysteresis and increase the service life of the sensor.
[0007] To achieve the above object, a first aspect of the present invention provides a method for preparing a fiber grating humidity sensor, comprising the following steps:
[0008] preparing a moisture-sensitive coating modification solution containing potassium acetate and polyacrylic acid;
[0009] Immersing the polyimide-coated fiber Bragg grating into the moisture-sensitive coating modification solution for surface modification;
[0010] Annealing the fiber Bragg grating after the surface modification to obtain a cured polyimide coated grating;
[0011] The cured polyimide coated grating is subjected to stress release treatment to obtain a fiber grating humidity sensor.
[0012] Furthermore, in the moisture-sensitive coating layer modification solution, the concentration of the polyacrylic acid is 12 wt % to 20 wt %.
[0013] Furthermore, in the moisture-sensitive coating layer modification solution, the concentration of potassium acetate is 1 wt % to 2 wt %.
[0014] Furthermore, the surface modification treatment is performed at a temperature of 20 to 30° C., a humidity of 40% RH to 60% RH, and a treatment time of 4 to 6 hours.
[0015] Furthermore, the polyimide-coated fiber Bragg grating is prepared by the following method: immersing the pretreated fiber Bragg grating in a polyimide slurry, and forming a polyimide coating layer on the surface of the fiber Bragg grating by pulling coating and heating curing; the pretreatment is to perform hydroxylation treatment and silane coupling agent modification treatment on the surface of the fiber Bragg grating.
[0016] Furthermore, the pretreatment is performed by the following method: firstly placing the fiber Bragg grating with the coating removed in a piranha solution for surface hydroxylation treatment, and then placing the fiber Bragg grating in a silane coupling agent solution for silane coupling agent modification treatment.
[0017] Furthermore, the silane coupling agent is aminopropyltriethoxysilane, such as WD-50, KH-550.
[0018] Furthermore, the annealing treatment is performed at a temperature of 200 to 220° C. and for a time of 2 to 4 hours.
[0019] Furthermore, the stress release treatment is performed at a temperature of 20 to 30° C., a humidity of 40% RH to 60% RH, and a treatment time of more than 20 hours.
[0020] A second aspect of the present invention provides a fiber grating humidity sensor obtained by any of the preparation methods described above.
[0021] Compared with the prior art, the present invention has the following technical effects:
[0022] The preparation method of a fiber Bragg grating humidity sensor of the present invention comprises the following steps: before annealing treatment, immersing a polyimide-coated fiber Bragg grating into a moisture-sensitive coating modification solution for surface modification treatment; the polyacrylic acid in the modification solution is used as a wire adhesive, so that the polyimide coating layer and the fiber grating region cladding (Si material) have a better bonding effect; in addition, the polyacrylic acid and polyimide in the modification solution can form an amphoteric copolymer network, which can increase the hydrophobic angle of the surface of the polyimide film (optical fiber coating material) and allow water droplets to quickly leave the surface of the optical fiber coating layer; and the potassium acetate in the modification solution can increase the internal pore space of the polyimide coating layer, thereby increasing the specific surface area of the material, increasing the expansion volume of the polyimide coating layer after absorbing water molecules during subsequent humidity sensing, and the rate at which water vapor passes through the coating layer, thereby improving the response speed of the sensor and reducing the wet hysteresis, so as to improve the sensitivity of the sensor. In addition, the volume thermal expansion coefficient of the polyacrylic acid in the modified solution is small, which can effectively inhibit the thermal volume expansion of the polyimide coating layer, prevent the polyimide coating layer from detaching from the fiber grating cladding layer due to long-term exposure to high temperature and high humidity, and improve the stability of the adhesion between the polyimide coating layer and the optical fiber of the fiber grating humidity sensor, thereby increasing the service life of the sensor.
[0023] The fiber grating humidity sensor of the present invention uses polyimide as the humidity-sensitive material. Polyimide has low hysteresis and high temperature resistance and can remain stable under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 is a SEM image of the optical fiber end face of the optical fiber Bragg grating humidity sensor prepared in the comparative example of the present invention;
[0026] Figure 2 is a SEM image of the optical fiber end face of the fiber grating humidity sensor prepared in Example 1 of the present invention;
[0027] Figure 3This is a test result diagram of the humidity sensitivity coefficient of the fiber grating humidity sensor prepared in Example 1 of the present invention between 30% RH and 100% RH;
[0028] Figure 4 This is a graph showing the long-term stability test results of the fiber grating humidity sensor prepared in Example 1 of the present invention between 30% RH and 100% RH. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0031] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass described in the description of the embodiments of the present invention may be μg, mg, g, kg, or other mass units known in the biochemical field.
[0032] The embodiment of the present invention provides a fiber Bragg grating humidity sensor and a preparation method thereof, comprising the following steps:
[0033] (1) preparing a moisture-sensitive coating layer modification solution containing potassium acetate and polyacrylic acid;
[0034] (2) immersing the polyimide-coated fiber Bragg grating into a moisture-sensitive coating modification solution for surface modification;
[0035] (3) annealing the surface-modified fiber Bragg grating to obtain a cured polyimide-coated grating;
[0036] (4) The cured polyimide coated grating is subjected to stress release treatment to obtain a fiber grating humidity sensor.
[0037] In the above step (1), the concentration of polyacrylic acid in the moisture-sensitive coating modification solution is 12wt% to 20wt%. If the concentration of polyacrylic acid is greater than 20wt%, the viscosity of the modified solution will be too high, making it impossible for potassium acetate to be evenly dispersed, and its corrosion effect will be weakened, ultimately resulting in the modification failing to achieve the expected effect. If the concentration of polyacrylic acid is less than 12wt%, its bonding effect is poor, and the coating layer and the optical fiber grating cladding layer cannot be well combined.
[0038] In addition, the concentration of potassium acetate in the moisture-sensitive coating layer modification solution is 1wt% to 2wt%. If the concentration of potassium acetate is greater than 2wt%, its corrosion effect is too strong and irreversible damage will be caused to the polyimide polymer film; if the concentration of potassium acetate is less than 1wt%, the corrosion effect produced by it cannot improve the porosity well, thereby failing to improve the ability of the polymer film to absorb and dehumidify moisture, and failing to improve the sensitivity of the sensor.
[0039] The polyacrylic acid in the moisture-sensitive coating modification solution contains a carboxyl strong polar group. Before the polyimide coating is annealed, it is immersed in the modification solution. The polyacrylic acid in the modification solution can be used as a wire adhesive, so that the polyimide coating and the optical fiber grating cladding (Si material) have a better bonding effect; in addition, the polyacrylic acid and polyimide in the modification solution can form an amphoteric copolymer network, which can increase the hydrophobic angle of the surface of the polyimide film (optical fiber coating material) and make water droplets quickly leave the surface of the optical fiber coating. In addition, the potassium acetate added to the moisture-sensitive coating modification solution can make the polyacrylic acid swell after mixing with the potassium acetate aqueous solution. The rate becomes larger, and the potassium acetate solution has a certain corrosiveness to the polymer polyimide film material, which can permanently increase the internal pore space of the polyimide polymer film (i.e., the polyimide coating layer), thereby increasing the specific surface area of the material, and increasing the expansion volume of the polyimide polymer film after absorbing water molecules during subsequent humidity sensing and the rate at which water vapor passes through the coating layer, thereby improving the response speed of the sensor and reducing the hysteresis, so as to improve the sensitivity of the sensor; in addition, the fiber grating humidity sensor of the present invention selects polyimide as the humidity-sensitive material, and polyimide has low hysteresis and high temperature resistance, and can remain stable under high temperature conditions.
[0040] In addition, the volume thermal expansion coefficient of the polyacrylic acid in the modified solution is small, which can effectively inhibit the thermal volume expansion of the polyimide polymer film, prevent the polyimide coating and the optical fiber grating cladding from being separated under high temperature and high humidity conditions for a long time, and improve the stability of the adhesion between the polyimide coating and the optical fiber of the fiber grating humidity sensor, thereby increasing the service life of the sensor.
[0041] In the embodiment of the present invention, the moisture-sensitive coating layer modification solution can be specifically prepared according to the following method:
[0042] (101) Dissolve 0.055–0.19 g of potassium acetate in 3.895 g of deionized water and stir magnetically for 5 min to completely dissolve it;
[0043] (102) 1.57–5.42 g of a 35 wt % polyacrylic acid (PAA, 523925) aqueous solution was sonicated for 5 min to obtain a uniformly dispersed polymer solution;
[0044] (103) The solutions obtained in steps (101) and (102) were placed in the same beaker and mixed, and magnetically stirred at 600 rpm for 15 min to obtain a moisture-sensitive coating layer modified solution.
[0045] In the above step (2), the polyimide-coated fiber Bragg grating can be prepared by the following method: immersing the pretreated fiber Bragg grating in a polyimide slurry, and forming a polyimide coating layer on the surface of the fiber Bragg grating by pulling the coating and heating and curing; the pretreatment is to perform hydroxylation treatment and silane coupling agent modification treatment on the surface of the fiber Bragg grating. The hydroxylation treatment can make the optical fiber surface more hydrophilic, enhance the surface reaction efficiency of the grating periodic structure and the subsequent stability of its combination with the humidity-sensitive film. The silane coupling agent modification treatment can make the silicon-based material subsequently couple with the humidity-sensitive film, further enhancing the bonding force between the humidity-sensitive film and the fiber grating area. The silane coupling agent can be aminopropyltriethoxysilane, such as WD-50, KH-550, etc.
[0046] In an embodiment of the present invention, the pretreatment is performed by the following method: firstly, the fiber Bragg grating with the coating removed is placed in a piranha solution for surface hydroxylation treatment, and then the fiber Bragg grating is placed in a silane coupling agent solution for silane coupling agent modification treatment. Specifically, the following steps are included:
[0047] (201) Open the fume hood and use a pipette to transfer 7 mL of 98% concentrated sulfuric acid slowly along the wall of the beaker into a 30 mL beaker;
[0048] (202) using a pipette to transfer 3 mL of 30% hydrogen peroxide solution to the beaker in step (201) along a glass stirring rod;
[0049] (203) the mixed solution obtained in step (202) was magnetically stirred at 180 rpm for 5 min to obtain 10 mL of a uniformly dispersed piranha solution;
[0050] (204) Fixing the grating area of the Bragg fiber grating after the coating layer is removed in a 50 mm curved glass surface dish groove, and transferring 0.5 mL of the evenly dispersed piranha solution obtained in step (203) to the grating area, and allowing it to react for 20 minutes;
[0051] (205) Pipette the piranha solution from the glass surface dish into a beaker, and use deionized water and alcohol to alternately rinse the Bragg grating area. After washing, use a hot air gun to dry it. A fiber Bragg grating with surface hydroxylation treatment is obtained;
[0052] (206) 7.2 mL of anhydrous ethanol, 2 mL of KH-550 (RSiY3), and 1.6 mL of deionized water were added to an iron container and magnetically stirred for 5 min;
[0053] (207) immersing the surface hydroxylated fiber Bragg grating region obtained in step (205) into the silane coupling agent solution of step (206) for 10 minutes;
[0054] (208) The grating in step (207) is taken out and placed in a 120° C. oven for 20 minutes to obtain a pretreated bare coated fiber Bragg grating.
[0055] The piranha solution in the embodiment of the present invention can effectively remove organic impurities on the grating surface. After hydroxylation treatment with the piranha solution, the optical fiber surface has stronger hydrophilicity, which can enhance the surface reaction efficiency of the grating periodic structure and the subsequent stability of its combination with the humidity sensitive film.
[0056] After step (208) is completed, the bare coated fiber Bragg grating is immersed in a polyimide slurry, and a polyimide coating layer is formed on the surface of the fiber Bragg grating by pulling the coating and heating and curing. The polyimide slurry can be prepared using existing technology. The specific preparation process of the polyimide slurry in the embodiment of the present invention refers to CN112409265A. The embodiment of the present invention uses 3,3',4,4'-biphenyltetracarboxylic dianhydride (BDPA) and 2-(4-aminophenyl)-5-aminobenzimidazole (PABZ) as raw materials for dianhydride and diamine, and the copolymer is 4,4'-diaminodiphenyl ether (ODA). ODA and BDPA with equal molar mass are stirred to completely prepare a polyamic acid solution, and then the target polyimide slurry is prepared by two-step thermal imidization. The embodiment of the present invention can control the water absorption rate of the polyimide slurry by selecting specific dianhydrides and diamines, thereby improving the humidity sensitivity coefficient of the polyimide optical fiber coating layer and improving the sensitivity of the sensor.
[0057] In the embodiment of the present invention, the polyimide coating layer can be specifically prepared according to the following steps:
[0058] (209) The bottom of a 0.5 mL transparent centrifuge tube was pierced using a micro-grinder with a drill bit of 1 mm in diameter;
[0059] (210) A customized hollow glass tube (length L: 10 mm, inner diameter r: 0.5 mm, outer diameter R: 1 mm) is vertically fixed to the bottom of the centrifuge tube in step (209) using ultraviolet glue;
[0060] (211) aligning the central axis of the centrifuge tube and the ceramic hot pressing ring, and fixing them with a bracket just below the mechanical arm of the immersion and lifting coating machine;
[0061] (212) The optical fiber Bragg grating processed in step (208) is passed through a ceramic hot pressing ring, a centrifugal tube and a hollow glass tube in sequence, and the optical fiber head is suspended on a mechanical arm of a dipping and pulling coating machine;
[0062] (213) Manually control the mechanical arm of the dip-pull coating machine to adjust the position of the optical fiber grating area, set the starting and ending points of the pull, the starting point is the middle of the centrifuge tube, the end point is the middle of the ceramic hot pressing ring, record the pull height h, and place the grating area at the starting point;
[0063] (214) injecting the polyimide slurry into the centrifuge tube fixed in position in step (213), and the first immersion of the gate area begins, and the immersion time is 1 minute;
[0064] (215) Adjust the immersion coating machine to the manual operation mode, set the pulling height to the value h recorded in step (213), the pulling speed to 180 μm / s, and the descending speed to 180 μm / s. After the grating is pulled to the specified height h, stay for 15 seconds and start to descend to the origin position;
[0065] (216) Repeat step (215) twice to complete the first three layers of coating. The first three layers of coating are manually completed to ensure the uniformity of the moisture-sensitive film combined with the optical fiber cladding;
[0066] (217) The immersion coating machine was adjusted to the automatic operation mode, and the pulling speed was set to 400 μm / s, the descending speed was set to 400 μm / s, the immersion time was set to 30 s, the dwell time was set to 10 s, and the number of cycles was set to 6 to complete the coating.
[0067] The fiber Bragg grating with a polyimide coating prepared in the embodiment of the present invention has a coating thickness of 15 μm and an outer diameter of 155 μm at the grating, which is thinner than the original coating diameter.
[0068] After the polyimide coating is completed, the fiber Bragg grating needs to be immediately immersed in the moisture-sensitive coating modification solution for modification treatment. In the implementation of the present invention, the modification treatment temperature is 20-30°C, the humidity is 40%RH-60%RH, and the treatment time is 4-6h. By controlling the modification temperature, modification humidity and modification time, the properties of the modification solution can be kept stable and the modification effect can be achieved to the best.
[0069] In the above step (3), the annealing temperature is 200-220°C and the time is 2-4 hours. The annealing temperature of the polyimide material can affect its thermal expansion coefficient and water absorption rate. In this annealing temperature range, the influence of thermal expansion on humidity expansion can be effectively reduced, the influence of hysteresis effect at high temperature can be reduced, and internal stress can be eliminated to a certain extent.
[0070] In the above step (4), the temperature of the stress release treatment is 20-30°C, the humidity is 40%RH-60%RH, and the treatment time is more than 20 hours. By controlling the temperature, humidity and time of the stress release treatment, the stress caused by the processing can be fully released.
[0071] The following uses multiple specific embodiments to illustrate a fiber Bragg grating humidity sensor and its preparation method according to an embodiment of the present invention. In the following multiple specific embodiments, the specific preparation process of the polyimide-coated fiber Bragg grating can be prepared according to the above method, and no further description is given. The following multiple specific embodiments only study the effect of the humidity-sensitive coating layer modification solution with different material contents on the performance of the prepared fiber Bragg grating humidity sensor.
[0072] Example 1
[0073] Embodiment 1 of the present invention provides a fiber Bragg grating humidity sensor and a method for preparing the same, comprising the following steps:
[0074] (a) Dissolve 0.105 g potassium acetate in 3.895 g deionized water and stir magnetically for 5 min to completely dissolve it;
[0075] (b) 3 g of a 35 wt % polyacrylic acid (PAA, 523925) aqueous solution was ultrasonicated for 5 min to obtain a uniformly dispersed polymer solution;
[0076] (c) The solutions obtained in steps (a) and (b) were placed in a beaker and mixed, and magnetically stirred at 600 rpm for 15 min to obtain a moisture-sensitive coating layer modified solution.
[0077] (d) immersing the polyimide-coated fiber Bragg grating into 10 mL of the moisture-sensitive coating modification solution of step (c) for modification; the modification treatment is: treating in an ultra-clean room experimental environment at 25° C. and 60% RH for 4 hours;
[0078] (e) annealing the modified fiber Bragg grating in an oven at 220° C. for 4 h to obtain a cured polyimide coated grating;
[0079] (f) The cured polyimide coated grating is placed in a clean room experimental environment at 25° C. and 60% RH for 24 hours, and a fiber Bragg grating humidity sensor is obtained after the stress is released.
[0080] Example 2
[0081] The difference between the above method and Example 1 is that the amount of potassium acetate used in step (a) is 0.055 g, the amount of polyacrylic acid used in step (b) is 1.57 g, and the other process conditions are the same.
[0082] Example 3
[0083] The difference between the above method and Example 1 is that the amount of potassium acetate used in step (a) is 0.19 g, the amount of polyacrylic acid used in step (b) is 5.42 g, and the other process conditions are the same.
[0084] Comparative Example
[0085] The difference between this embodiment and the first embodiment is that the polyimide coated fiber Bragg grating is not treated with a moisture-sensitive coating layer modification solution, but is directly subjected to annealing and stress release treatment.
[0086] The fiber Bragg grating humidity sensors prepared in Example 1 of the present invention and the comparative example were subjected to high and low temperature cycle treatment for 6 times, and the specific treatment process was as follows:
[0087] (1) The sensors prepared in Example 1 of the present invention and the comparative example were respectively placed in a temperature and humidity test chamber (including a humidity generator (L-LRH) and a cold mirror type precision dew point meter) and installed, and the sensors were initially tested under normal atmospheric conditions in the laboratory;
[0088] (2) Adjust the test chamber temperature to A (the initial value of A is -30°C) and maintain it for 10 minutes to allow the test sample and the chamber to reach a stable temperature state and maintain this temperature state for 30 minutes;
[0089] (3) Increase the temperature to 160°C and maintain it at this temperature for 30 min;
[0090] (4) Repeat steps (2) and (3) 6 times;
[0091] (5) Adjust the temperature in the test chamber back to room temperature and maintain it for 1 hour. Then open the door and allow the sensor to return to a stable state under normal laboratory atmospheric conditions.
[0092] After high and low temperature cycle treatment, the end faces of the fiber grating humidity sensor prepared in Example 1 of the present invention and the comparative example were subjected to SEM analysis. The SEM results are as follows: Figure 1 , Figure 2 shown. Figure 1This is the fiber end face diagram of the fiber grating humidity sensor prepared in the comparative example. Figure 2 This is a fiber end face diagram of the fiber grating humidity sensor prepared in Example 1 of the present invention. Figure 1 There is obvious separation between the polyimide coating and the optical fiber cladding. Figure 2 The optical fiber cladding and the polyimide coating are stably bonded, indicating that the stability of the direct bonding between the polyimide coating and the optical fiber cladding interface can be significantly enhanced after the polyimide-coated fiber Bragg grating is treated with a moisture-sensitive coating modification solution.
[0093] The humidity sensitivity coefficient of the fiber grating humidity sensor prepared in Example 1 of the present invention is tested between 30% RH and 100% RH. The test process is as follows:
[0094] (1) The sensors prepared in Example 1 of the present invention and the comparative example were respectively placed in a temperature and humidity test chamber and installed, and the sensors were initially tested under normal atmospheric conditions in the laboratory;
[0095] (2) Adjust the test box temperature to 25°C and humidity B (the initial value of B is 25% RH) for 15 minutes to allow the sensor and the box to reach a stable temperature and humidity state, and record the channel center wavelength value stored in the optical performance monitoring module during the stable state period;
[0096] (3) Keep the temperature constant, increase the humidity to 35% RH, repeat step (2) and record the results;
[0097] (4) Keep the temperature constant, increase the humidity by 45% RH, repeat step (2) and record the results;
[0098] (5) Keep the temperature constant until the humidity reaches 55% RH, repeat step (2) and record the results;
[0099] (6) Keep the temperature constant until the humidity reaches 55% RH, repeat step (2) and record the results;
[0100] (7) Keep the temperature constant until the humidity reaches 65% RH, repeat step (2) and record the results;
[0101] (8) Keep the temperature constant until the humidity reaches 75% RH, repeat step (2) and record the results;
[0102] (9) Keep the temperature constant until the humidity reaches 85% RH, repeat step (2) and record the results;
[0103] (10) Keep the temperature constant until the humidity reaches 95% RH, repeat step (2) and record the results;
[0104] (11) Adjust the temperature in the test chamber back to normal temperature and humidity, maintain it for 1 hour, then open the door to allow the sensor to return to a stable state under normal laboratory atmospheric conditions.
[0105] Test results such as Figure 3 As shown, from Figure 3 It can be seen that the sensitivity of the fiber grating humidity sensor prepared in Example 1 of the present invention is 3.9pm / %RH, and the fitting degree reaches 0.9989. After testing the humidity sensitivity coefficient of the fiber grating humidity sensor prepared in the comparative example of the present invention between 30%RH and 100%RH, it is found that under the condition of the same thickness of the polyimide coating layer, the sensitivity coefficient of the fiber grating humidity sensor prepared in Example 1 of the present invention is about 4 times the sensitivity coefficient of the conventional polyimide coated humidity sensor (i.e., the humidity sensor prepared in the comparative example).
[0106] The long-term stability of the fiber grating humidity sensor prepared in Example 1 of the present invention between 30% RH and 100% RH was tested, and the test process was as follows:
[0107] 1) The sensor prepared in Example 1 of the present invention is placed in a temperature and humidity test chamber and installed, and the test piece is initially tested under normal atmospheric conditions in the laboratory;
[0108] (2) Adjust the test chamber temperature to 25°C and humidity B (the initial value of B is 35% RH) for 15 minutes to allow the test product and the chamber to reach a stable temperature and humidity state. Record the chamber temperature and humidity values and the sensor demodulated humidity values every 1 minute for 5 minutes, and save the central wavelength values of all channels stored in the optical performance monitoring module during the stable state period;
[0109] (3) Keep the temperature constant, increase the humidity to 55% RH, repeat step (2) and record the results;
[0110] (4) Keep the temperature constant, increase the humidity by 75% RH, repeat step (2) and record the results;
[0111] (5) Keep the temperature constant until the humidity reaches 95% RH, repeat step (2) and record the results;
[0112] (6) Adjust the temperature in the test chamber to normal temperature and humidity, maintain it for 1 hour, then open the door to allow the sensor to return to a stable state under normal laboratory atmospheric conditions;
[0113] Test results such as Figure 4 As shown, from Figure 4 It can be seen that the response value deviation of the fiber Bragg grating humidity sensor prepared in Example 1 of the present invention is within 1% RH, which indicates that the fiber Bragg grating humidity sensor prepared in Example 1 of the present invention has good stability in high humidity measurement and a long service life.
[0114] The embodiment of the present invention uses a moisture-sensitive coating modification solution to modify the unannealed polyimide coating, thereby enhancing the bonding stability between the optical fiber cladding and the polyimide coating, so that even if the sensor is exposed to a high humidity and high temperature environment for a long time, the polyimide coating of the sensor and the optical fiber cladding are not easily separated, thereby extending the service life of the sensor and improving its stability in a high humidity measurement environment. In addition, the sensitivity of the sensor can also be improved.
[0115] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.
Claims
1. A method for preparing a fiber Bragg grating humidity sensor, characterized in that: The following steps are involved: preparing a moisture-sensitive coating modification solution containing potassium acetate and polyacrylic acid; Immersing the polyimide-coated fiber Bragg grating into the moisture-sensitive coating modification solution for surface modification; Annealing the fiber Bragg grating after the surface modification to obtain a cured polyimide coated grating; The cured polyimide coated grating is subjected to stress release treatment to obtain a fiber grating humidity sensor.
2. The method for preparing a fiber Bragg grating humidity sensor according to claim 1, characterized in that: In the moisture-sensitive coating layer modification solution, the concentration of the polyacrylic acid is 12 wt % to 20 wt %.
3. The method for preparing a fiber Bragg grating humidity sensor according to claim 1, characterized in that: In the moisture-sensitive coating layer modification solution, the concentration of potassium acetate is 1 wt % to 2 wt %.
4. The method for preparing a fiber Bragg grating humidity sensor according to claim 1, characterized in that: The surface modification treatment is performed at a temperature of 20 to 30° C., a humidity of 40% RH to 60% RH, and a treatment time of 4 to 6 hours.
5. The method for preparing a fiber Bragg grating humidity sensor according to claim 1, characterized in that: The polyimide coated fiber Bragg grating is prepared by the following method: immersing the pretreated fiber Bragg grating in a polyimide slurry, forming a polyimide coating layer on the surface of the fiber Bragg grating by pulling coating and heating and curing; the pretreatment is to perform hydroxylation treatment and silane coupling agent modification treatment on the surface of the fiber Bragg grating.
6. The method for preparing a fiber Bragg grating humidity sensor according to claim 5, characterized in that: The pretreatment is performed by the following method: firstly placing the fiber Bragg grating with the coating removed in a piranha solution for surface hydroxylation treatment, and then placing the fiber Bragg grating in a silane coupling agent solution for silane coupling agent modification treatment.
7. The method for preparing a fiber Bragg grating humidity sensor according to claim 6, characterized in that: The silane coupling agent is aminopropyltriethoxysilane.
8. A method for preparing a fiber Bragg grating humidity sensor according to any one of claims 1 to 7, characterized in that: The annealing treatment is carried out at a temperature of 200 to 220° C. and for a time of 2 to 4 hours.
9. A method for preparing a fiber Bragg grating humidity sensor according to any one of claims 1 to 7, characterized in that: The stress release treatment is performed at a temperature of 20 to 30° C., a humidity of 40% RH to 60% RH, and a treatment time of more than 20 hours.
10. A fiber Bragg grating humidity sensor, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Diamine monomer containing bisbenzoxazole unit and preparation method of diamine monomer
CN112409265A
A humidity / salinity sensor sensitive membrane based on a carbonyl powder doped polymer swelling material, a preparing method thereof and applications of the sensitive membrane
CN106053328A
Optical fiber humidity sensor based on lithium chloride-doped polyimide and preparation method thereof
CN108827916A
Modified polyimide hollow fiber membrane and application thereof
CN117225219A
Optical fiber humidity sensor, and humidity detecting system and respiration detecting system using the same
JP2003130863A
Cited By
Center twisting type ultra-weak fiber bragg grating temperature and humidity stranded yarn and application method thereof
CN119756483A
Ultra-weak fiber grating multi-parameter sensing strand and application method thereof
CN119958615A
